Strengthening entrepreneurial management and digital marketing capabilities of MSMEs through social media optimization training - Yudha Herlambang Cahya Pratama; Herwin Ardianto; Mohammad Al Hafidz; Puspa Ari Khairunisa'; Rika; Shinta Cahyani Putri; Marsanda Ayunda Sari (University of Merdeka Malang, 2025)
This community service activity aims to enhance the capacity of MSME actors fostered by the Economic and Entrepreneurship Council (Majeko) under the Muhammadiyah Branch Leadership (PCM) of Rungkut Surabaya in the aspects of entrepreneurship management and digital marketing. The main problems faced by the partners include weak business management, low entrepreneurial motivation, and suboptimal utilization of social media as a promotional tool. The activity involved 30 MSME participants and was carried out in the form of intensive training. The materials provided covered business plan preparation, financial recording, and social media–based digital marketing strategies. The evaluation results showed that 87 percent of participants stated the training was highly beneficial, and 60 percent began actively promoting their products through social media. Other identified impacts included increased business motivation and the emergence of a digital community among participants. This activity not only enhanced technical skills but also fostered awareness of the importance of digital transformation in MSME development. Overall, this activity has provided tangible benefits for Majeko MSMEs in the form of improved managerial capacity, greater self-reliance in business management, and expanded market reach through the implementation of sustainable digital marketing strategies.